Impacts of process modifications - A case study at Volvo Cars Corporation - Andersson, Sebastian (My University, 2012)
A process is commonly viewed as the series of actions carried out to bring out a result.Improving a process, or sub process, is of course very desirable for any kind of engineer. In this thesis, the author investigates whether a change to improve a sub process also could benefit other related sub processes indirectly. A case study is performed with a group of engineers at Volvo Cars Corporation to examine the impacts a small change to their data management process brings to their workflow. The effects of the changes are measured by gathering data using surveys and interviews. Using these opinions and thoughts that the group and their co-workers have, it is concluded that the sub process change was beneficial and has the potential of bringing additional improvements to other sub processes.
Keywords: Datavetenskap (datalogi); Computer Science